Walkable city rules : 101 steps to making better places - Speck, Jeff (Washington, DC : Island Press, 2018)
'Nearly every US city would like to be more walkable-for reasons of health, wealth, and the environment-yet few are taking the proper steps to get there. The goals are often clear, but the path is seldom easy. Jeff Speck's follow up to his bestselling Walkable City is the resource that cities and citizens need to usher in an era of renewed street life. Walkable City Rules is a doer's guide to making change in cities, and making it now. The 101 rules are practical yet engaging-worded for arguments at the planning commission, illustrated for clarity, and packed with specifications as well as data. For ease of use, the rules are grouped into 19 chapters that cover everything from selling walkability, to getting the parking right, escaping automobilism, making comfortable spaces and interesting places, and doing it now! Walkable City was written to inspire; Walkable City Rules was written to enable. It is the most comprehensive tool available for bringing the latest and most effective city-planning practices to bear in your community. The content and presentation make it a force multiplier for place-makers and change-makers everywhere.' --Publisher description.
Includes bibliographical references (pages 247-271) and index.
Keywords: Central business districts -- United States -- Planning; Pedestrian areas -- United States -- Planning; Urban renewal -- United States; City planning -- United States